Penurunan Kadar Besi Dengan Variasi Luas Trap Cascade Aerator Dan Debit Pada Air Gambut - Muhammad Irwan Syahputra; Syarfi Daud; Dewi Fitria (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Fe content is a metal that is quite high in peat water. One technology that can be applied to remove Fe content is aeration. Aeration is the process of adding oxygen to water so that it can cause Fe oxidation reaction which will then cause Fe(OH)3 deposition. This study aims to determine the ability of the cascade aerator to remove Fe content in peat water with discharge variations of 4, 4,5, and 5 l/min with a variation of the trap area of 1,8 m2 and 2 m2. Also calculated is the value of the gas transfer coefficient (KLa) in the aeration process using a cascade aerator. Fe content before aeration was 1,22 mg/l. The results showed that the highest efficiency of removal of Fe content occurred at a discharge of 5 l/minute at a trap area of 2 m2 with an efficiency of 81,16%. The highest gas transfer coefficient value was obtained at a discharge of 5 l/minute on a 2 m2 trap area of 0,111/minute. The research results obtained have met the clean water quality standards PERMENKES RI No. 32 years 2017. Keywords: Cascade Aerator, Iron (Fe), Discharge, Trap Area, The Coefficient Of Gas Transfer (KLa).